Comparing Westminster - Rhodes, R. A. W.; Wanna, John.; Weller, Patrick Moray (Oxford : Oxford University Press, 2009)
This text explores how governmental elites understand the Westminster systems of Australia, Britain, Canada, New Zealand, and South Africa. It concludes that Westminster is a flexible family of ideas that is useful for many purposes and survives and, even thrives, because of its varied uses to elite actors.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Legislative bodies; Comparative government; Australia -- Politics and government; Great Britain -- Politics and government; Canada -- Politics and government; New Zealand -- Politics and government; South Africa -- Politics and government